Do Initial Symptom Factor Scores Predict Subsequent Impairment Following Concussion?. (March 2020) - Cohen, Paul E.; Sufrinko, Alicia; Elbin, Robert J.; Collins, Michael W.; Sinnott, Aaron M.; Kontos, Anthony P.
Abstract : Objective: Symptom factors present during the first week following concussion may predict subsequent concussion outcomes and recovery duration. We hypothesized that a high loading on cognitive-fatigue-migraine and somatic factors would be predictive of neurocognitive impairment following concussion. We also hypothesized that the affective factor would be related to vestibular symptoms and impairment. Design: Prospective repeated measures. Setting: Concussion specialty clinic. Participants: Athletes aged 13 to 20 years diagnosed with a concussion within the past 7 days. Independent Variable: Symptom factors at the initial visit 1 to 7 days after injury. Main Outcome Measure: Symptom factor score, neurocognitive testing, and vestibular/ocular motor assessment at the second visit (2-4 weeks after injury). Results: The somatic symptom factor from the initial visit was significant ( P < 0.05) in all vestibular/ocular screening components ( P < 0.05) but not neurocognitive test performance ( P > 0.05) at the second visit. The cognitive-migraine-fatigue and affective symptom factors predicted symptom burden at the second visit ( P < 0.001) but did not predict recovery time ( P = 0.200). Conclusions: The somatic symptom factor during the first week after injury predicted symptom provocation during vestibular/ocular screening at 2 to 4 weeks after injury. Specifically, higher scores on somatic symptom factor at the initial visit predicted worse symptom reporting for all vestibular/ocular screening components at the second visit. Patients with higher scores on the cognitive-migraine-fatigue and affective symptom factors at the initial visit predicted total symptom burden at the second visit.